Proceedings 2019 Network and Distributed System Security Symposium 2019
DOI: 10.14722/ndss.2019.23442
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Attacks to the 4G and 5G Cellular Paging Protocols Using Side Channel Information

Abstract: The cellular paging (broadcast) protocol strives to balance between a cellular device's energy consumption and quality-of-service by allowing the device to only periodically poll for pending services in its idle, low-power state. For a given cellular device and serving network, the exact time periods when the device polls for services (called the paging occasion) are fixed by design in the 4G/5G cellular protocol. In this paper, we show that the fixed nature of paging occasions can be exploited by an adversary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 17 publications
0
66
0
Order By: Relevance
“…The considered technologies are heavily used in IoT. A large majority have studied security attacks considering multiple wireless communication technologies, such as Wi-Fi, Bluetooth, RFID, WiMax, UMTS, LTE, and WSNs 5 [88]- [90], whereas others have chosen to survey attacks in one particular wireless communication technology, e.g., Wi-Fi [91]- [94], Bluetooth [95]- [102], ZigBee (or IEEE 802.15.4) [103]- [107], RFID [108]- [114], 6LoWPAN (Ipv6 over Low-Power Wireless Personal Area Networks) [115]- [118], LoRaWAN [119]- [121], Zwave and Thread [122], WiMax [123]- [128], and 4G (i.e., LTE) or 5G [129]- [131]. Table 1 summarizes the three IoT security attack research directions (i.e., RD1, RD2, and RD3), with respect to the considered IoT applications (Column 2), IoT wireless communication technologies (Column 3), IoT network architectures (Column 4), and IoT security services (Column 5).…”
Section: Existing Iot Attack Research Directionsmentioning
confidence: 99%
“…The considered technologies are heavily used in IoT. A large majority have studied security attacks considering multiple wireless communication technologies, such as Wi-Fi, Bluetooth, RFID, WiMax, UMTS, LTE, and WSNs 5 [88]- [90], whereas others have chosen to survey attacks in one particular wireless communication technology, e.g., Wi-Fi [91]- [94], Bluetooth [95]- [102], ZigBee (or IEEE 802.15.4) [103]- [107], RFID [108]- [114], 6LoWPAN (Ipv6 over Low-Power Wireless Personal Area Networks) [115]- [118], LoRaWAN [119]- [121], Zwave and Thread [122], WiMax [123]- [128], and 4G (i.e., LTE) or 5G [129]- [131]. Table 1 summarizes the three IoT security attack research directions (i.e., RD1, RD2, and RD3), with respect to the considered IoT applications (Column 2), IoT wireless communication technologies (Column 3), IoT network architectures (Column 4), and IoT security services (Column 5).…”
Section: Existing Iot Attack Research Directionsmentioning
confidence: 99%
“…So far, previous studies found vulnerabilities in the specification ranging from privacy to denial of service attacks [38]. Privacy attacks can localize and track a user [43], [25], [44] or infer the visiting websites [30], [28]. Further, attacks can exploit protocol vulnerabilities of the phone [43], [24] or exhaust resources [46] for a denial of service.…”
Section: Related Workmentioning
confidence: 99%
“…Man-in-the-middle attacks are possible on both 3G [34] and 4G/LTE [35]. Eavesdropping attacks against the 4G network can also allow an attacker to recover the IMSI number of targets [36]. Other techniques have also been investigated where IMSI numbers can be obtained over WiFI [37].…”
Section: F Non-vehicle Communicationmentioning
confidence: 99%